Clinical, Histophatological, Laboratory, and Elastographic Findings and Treatment Outcome in Patients with Autoimmune Hepatitis in Sari, Iran - Mahboobe Ebrahimi; Hafez tirgar Fakheri; Tarang Taghvaei; Iradj Maleki; Vahid Hosseini; Arash Kazemi Veisari; Zohre Bari; Hajar Shokri-Afra; Sepehr tirgar Fakheri (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Autoimmune hepatitis is a chronic liver inflammatory disease of unknown etiology that is more common in women. The goal of this study was to investigate the clinical, histopathological, laboratory, and elastography findings and outcome in patients with autoimmune hepatitis and verifying the factors associated with treatment response in Sari, Iran. Materials and methods: This research is a descriptive study in which demographic, clinical, histopathological, laboratory and elastographic information of 136 autoimmune hepatitis patients referred to Imam Khomeini Hospital and specialized gastrointestinal clinics in Sari during the years 2019-2021 was recorded in a pre-designed questionnaire. Results: In the study of the relationship between demographic, laboratory, histopathological, elastographic, and clinical factors with response to treatment, only prothrombin time (PT) and platelet (PLT) count had a significant relationship with response to treatment (p < 0.05). In fact, thrombocytopenia and high PT led to poor treatment response and high PT was associated with a higher probability of recurrence. There was also a significant relationship between cirrhosis and non-cirrhosis at the time of diagnosis with response to treatment (p < 0.05). People with cirrhosis experienced less response to treatment. None of the factors mentioned were related to the new cirrhosis (p < 0.05). In the study of the relationship between the results of the initial and subsequent liver fibroscan during the follow-up, the reduction of fibrosis following treatment was clearly seen. Conclusion: Liver elastography is recommended for fibrosis evaluation during treatment and follow-up.